Personification in EFL learners’ academic writing: A cognitive linguistic stance - Belkhir, Sadia (Glottodidactica, 2021)
The paper offers a report of a small-scale corpus investigation into some advanced EFL learners’ use of personification in academic writing within a higher education context (Mouloud Mammeri University). Its main objective is to shed light on the extent of the occurrence of this phenomenon in their writings. The question raised is whether the examination of their dissertations would reveal extensive use of personification. Conceptual Metaphor Theory constitutes the theoretical framework featuring in this research. Relying on the Metaphor Identification Procedure (MIP) (Pragglejaz Group 2007), six master’s dissertations are selected for examination, and a quantitative analysis of the identified metaphorically used words is conducted. The results of the study reveal an overwhelming manifestation of personification. These findings may constitute a small contribution to the field of education, as offering useful data to educational practitioners and researchers.